2009
DOI: 10.1097/prs.0b013e3181a0746e
|View full text |Cite
|
Sign up to set email alerts
|

Discharge Practices, Readmission, and Serious Medical Complications following Primary Cleft Lip Repair in 23 U.S. Children’s Hospitals

Abstract: A number of factors related to the hospital, surgeon, patient, and patient's family bear consideration in deciding the timing of discharge after primary cleft lip repair. The most clinically important factor appears to be the overall preexisting medical status of the patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 9 publications
4
34
1
Order By: Relevance
“…Three studies 19,33,34 were included in otolaryngology, 2 focusing on tracheotomy and 1 on cleft lip repair. Both tracheotomy articles considered only hospital volume, and the study on cleft lip repair evaluated both surgeon and hospital volume.…”
Section: Otolaryngology or Craniofacial Surgerymentioning
confidence: 99%
“…Three studies 19,33,34 were included in otolaryngology, 2 focusing on tracheotomy and 1 on cleft lip repair. Both tracheotomy articles considered only hospital volume, and the study on cleft lip repair evaluated both surgeon and hospital volume.…”
Section: Otolaryngology or Craniofacial Surgerymentioning
confidence: 99%
“…36 The length of stay after repair of cleft palate can be affected by hospital type and setting, surgeon experience and volume, and patient-family resources. 2 Compared to general hospitals and nonaccredited children's hospitals, pediatric hospitals demonstrated a significantly shorter length of stay, despite treating patients with more comorbidities. 31,36 Teaching hospitals, historically considered to be more costly compared with nonteaching hospitals, 36,37 are comparable to their nonteaching counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Integral to any changes in traditional practices of patient care is a careful scrutiny of outcomes from a quality and safety perspective. Due to a change in inpatient duration of hospital stay through the 1980s, a series of audits regarding the complication rates of short-stay were performed (7)(8)(9)(10)(11)(12)(13). These authors suggested no significant complications were found with shorter hospital stays.…”
Section: Resultsmentioning
confidence: 99%
“…A multicentre study analyzing cleft lip repair discharge practices involving 2558 patients over a five-year period was performed by Hopper et al (10) and revealed that 72% of patients were being managed with an overnight inpatient stay postoperatively. On review of ambulatory outcomes, compared with inpatient stay outcomes, these authors found no significant differences between the groups and concluded that serious postoperative medical complications occurred rarely (1.1%), and that readmission to hospital was a rare event (1.88%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation